Children’s Self-Regulation in Norway and the United States: The Role of Mother’s Education and Child Gender Across Cultural Contexts - Lenes, Ragnhild; Gonzales, Christopher R.; Størksen, Ingunn; McClelland, Megan M. (Frontiers in Psychology, 2020)
Self-regulation develops rapidly during the years before formal schooling, and it helps lay the foundation for children`s later social, academic, and educational outcomes. However, children`s self-regulation may be influenced by cultural contexts, sociodemographic factors, and characteristics of the child. The present study investigates whether children`s levels of self-regulation, as measured by the Head-Toes-Knees-Shoulders (HTKS) task, are the same in samples from Norway (Mage = 5.79; N = 243, 49.4% girls) and the United States (U.S.) (Mage = 5.65; N = 264, 50.8% girls) and whether the role of mother`s education level and child gender on children`s self-regulation differ across the two samples. Results showed that Norwegian and U.S. children had similar levels of self-regulation. Mother`s education level significantly predicted children`s self-regulation in the U.S. sample but not in the Norwegian sample, and this difference across samples was significant. Girls had a significantly higher level of self-regulation than boys in the Norwegian sample, but there were no gender differences in the U.S. sample. However, the effect of child gender on self-regulation did not differ significantly across the two samples. Results highlight the importance of cross-cultural studies of self-regulation.